Islamic Values in Life Skills Education: Fostering Global Competence and Moral Integrity - Ritonga, Mahyudin; Julhadi, Julhadi; Abdulaziz, Hussein Abdulqader (AT-TA'LIM, 2025)
Islamic values-based life skills education plays a crucial role in shaping students' character to be well-prepared for global challenges, particularly in the dynamic modern era. This research aims to explore the integration of Islamic values-based life skills education at SMP IT Sekolah Alam Ar-Royyan and its impact on character development, especially in terms of discipline, responsibility, honesty, and independence. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews, participatory observation, and documentation from the school principal, teachers, and students. The data analysis technique employed is thematic analysis to identify key patterns and findings. The results indicate that programs such as Daurah Quran, project-based learning, Super Camp, and the Ar-Royyan Trip effectively foster students' life skills aligned with Islamic values, strengthening their morality and integrity in facing global challenges. However, this research has limitations regarding the scope and observation period, suggesting that future studies conduct comparative research in other schools and explore the development of digital skills based on Islamic values in life skills education in the modern era.